CARACTERIZAÇÃO E AVALIAÇÃO DA ATIVIDADE LARVICIDA DO ÓLEO ESSENCIAL DO Zingiber officinale Roscoe (GENGIBRE) FRENTE AO MOSQUITO Aedes aegypti - Silva, Andreson Leandro Santana (2012)
Looking for the chemical alternative control against the Aedes aegypti mosquito, several researches are developed and stimulated aiming discover new insecticide substances of vegetal origin. In this work, from the extraction and analytical study of the essential oil of the rhizomes of the Zingiber officinale Roscoe, the larvicidal effect of the oil against larvas in third phase of the mosquito Aedes aegypti (Linnaeus, 1792) was analyzed. The essential oil was extracted quantitatively by hydrodistilation. The essential oil physical-chemical proprieties (density, refraction rate, solubility, color and appearance) was determined. The oil was analytically characterized by infra-red (FTIR) and gas chromatography coupled to spectrometer of mass (CG-EM). The oil s CL50 was calculated from the Reed-Muench (1938) and Pizzi (1950) methods, respectively. The oil yield was 0.52% m/v. 18 components were identified in the oil, and the major presence of α- zingiberene was confirmed by the spectroscopic technics. The essential oil got CL50 76.07 (±2,24) μg mL-1. The results indicate that the essential oil evaluated is compound by substances that propitiate larvicidal effect against Aedes aegypti.